Cuidado e cotidianidade : (des)encontros entre haitianos(as) e trabalhadores(as) nos serviços de saúde - Martins, Maria Angela Conceição (2021)
International migration, especially in the 21st century, presented important challenges for societies, including the development of public policies aimed at including these people in the countries of destination. In this migratory scenario, Brazil has been affirming itself as a place of passage for migrants of different nationalities. The state of Mato Grosso has received migrants from Haiti since 2012, apparently motivated by the humanitarian visa granted by Brazil and the offer of work, among other factors. In 2015, according to data from the Annual Social Information Ratio, 1,125 Haitians were in 19 municipalities in the state, including the capital. Among the issues surrounding the migratory phenomenon is health, understood from the perspective of the constitutional right to universality provided by the SUS to the emic sense of care constructed by workers and migrants. This study aimed to understand the relationship between Haitian migrant (a) and health professional in the daily meeting for the provision of health care. It is nourished by the expectation that capturing the perspectives of both in relation to subjective and objective factors, at the moment of care, can contribute to the reflection of health work in the migratory context, its weaknesses, potentialities and repercussions for the formulation of policies for the area. This is a qualitative study with a socioanthropological approach that used interviews with semi-structured script, observation of ethnographic character, photographic records and field diary notes as research instruments. Workers who were part of the health services of the capital of Mato Grosso and Haitians who had experience of service in the service network were selected. The data produced were analyzed based on hermeneutics, especially in heideggerian theoretical contributions, added to the ethics of care, understood in its ontic character, as being it cares; and ontological, revealing the values that guide the care performed by the being. The results suggested that health practice was permeated by social stigmas; institutional racism and a sense of invisibility; priority and exclusion from the perspective of migrants. On the part of the workers, communication difficulties and exclusionary conceptions were highlighted regarding the right to health. If, on the one hand, the listening of the two groups outlined a fragile health care, in its ontological conception; on the other hand, it is in this same daily scenario, through the relationship and coexistence between migrants and health workers, in their ontic sense, that there are possibilities of overcoming and potential transforming elements of health care.